Two degree of freedom vortex induced vibration tests of a riser model using spring bars - Tofa, M. Mobassher (2014)
Tests have been performed on a riser model with low mass ratio subjected to uniform flows in a towing tank at subcritical Reynolds numbers. Qualisys video motion capture system was used to measure VIV and Spring bars are used instead of commonly used parallel linkage mechanism for this kind of test. The circular cylinder of 100 mm in diameter and 1.5 m in length was towed vertically at constant speeds through the towing tank to simulate uniform current condition. Some key VIV parameters such as amplitude over diameter, lift and drag coefficients are presented against a non dimensional parameter known as reduced velocity to understand the effects of VIV on two degree of freedom system.The relative magnitude of the super-upper response branch vibration amplitudes are emphasised in this particular study. Results of this paper can be used as validation materials for CFD analysis that is very important to design riser system for oil and gas industry, also mentioned experiment procedure can be treated as a guide for future endeavour to perform similar kind of tests.